ELEMEN KONSTRUKTIVIS FILSAFAT ETIKA MULLA SHADRA - Shadra, Yasser Mulla (UIN Sunan Kalijaga Yogyakarta, 2022)
Abstrak Beberapa jenis konstruktivisme moral telah banyak dijelaskan para ahlinya. Secara epistemologis, konstruktivisme moral merupakan pengetahuan moral atau justifikasi yang diperoleh melalui penggunaan dan refleksi sudut pandangan praksis atau prosedur untuk menjelaskan sudut pandangan praktis tersebut. Secara semantik, konstruktivisme moral merupakan pandangan bahwa kebenaran moral dan makna diadasarkan pada syarat atau prosedur ini. Ada juga konstruktivisme moral metafisik yang berpendapat bahwa sifat dan wujud fakta dan sifat moral didasarkan pada ciri-ciri praktis dasar atau prosedurnya. Oleh kerana, secara praksis tradisi falsafah morah dipahami secara berbeda sebagaimana falsafah moral Mulla Shadra. Falsafah moral Mulla Shadra merupakan menggabungkan ciri-ciri peripatetik Islam dan tradisi mistik Islam. Kedua tradisi ini mengandung elemen konstruktivis yang penting. Yang pertama berakar dari Aristotelian dan yang terakhir berakar dari pengembangan para ahli mistik. Kedua merupakan contoh kajian unsur konstruktivis “Tiga Akar” Mulla Sadra. Kata Kunci: Mulla Shadra, Tiga Akar, Kontruktivisme Moral Abstract Moral constructivism have been defined by experts. Epistemological moral constructivism is the thesis that moral knowledge or justification is acquired through the use of and reflection on the practical point of view or the procedures designed to elucidate it. Semantic moral constructivism is the view that moral truths and meanings are grounded in these conditions or procedures. Whreas, metaphysical moral constructivism holds that the natures and existences of moral facts and properties are grounded in features of the practical standpoint or the procedures of its manifest. Since the practical point of view is understood differently in different traditions of moral philosophy, one finds Aristotelian, Humean, Kantian, Hegelian, Nietzschean, and other forms of moral constructivism. The moral philosophy of Mulla Sadra is one that combines features of the Islamic-peripatetic and Islamic mystical traditions. Both of these traditions contain important constructivist elements: first with roots in Aristotelian and second what is developed by the mystics. Examples of both are presented and discussed in the course of Three Roots constructivist elements of Mulla Sadra͛s. Keywords: Mulla Shadra, Three Roots, Moral, Contructivism